Tensile and Fatigue Test Simulation Analysis for Al 2017 and Al 2024 - Nailon, Carlson; mahmod, muhammad faisal (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Selecting a material aircraft component for the front leg seat requests a lot of investigation in their physical properties, such as strength, ductility, corrosion resistance which is also influenced by the material production process and part production process. There is various material that was used to manufacture aircraft front leg seats that is Aluminum alloys which Al 2017 and Al 2024. In this paper tensile testing and fatigue testing simulations of Al 2017 and Al 2024 had been conducted where the analysis was done in Ansys workbench at the same condition and load. These tests were completed by using two cylindrical dog-bone specimens by followed the geometry standard; which is ASTM E8-16a for tensile test simulation and ASTM E466-07 for fatigue test simulation. The tensile test and fatigue test simulations analysis is conducted with 100 kN force applied at one of the specimens ends and fixed support applies on another specimen ends.  In this study, the result obtained from the tensile test simulation shows Al 2024 has the higher yield strength and tensile ultimate strength with 280 MPa and 895.67 Mpa respectively. Meanwhile, fatigue test simulation determines that Al 2017 and Al 2024 have the same value for fatigue life value which is 1x10^8.  In terms of fatigue damage, Al 2024 has less fatigue damage with 4172.2 which means it has the lower safety factor which is 4.7198. Therefore, in this study, Al 2024 is more high strength and has excellent fatigue resistance.